A Meta-Analysis of TPB Model in Predicting Green Energy Behavior: The Moderating Role of Cross-Cultural Factors. Issue 2 (15th March 2023) - Kumar, Ganesh; Nayak, Jogendra Kumar
Abstract: Ajzen's "theory of planned behaviour" (TPB) is being widely used across different contexts in predicting consumers' behavioral patterns toward green energy use for the last decade. However, previous empirical studies have presented inconsistent results with respect to the magnitude of associations among TPB constructs. Therefore, to synthesize the diverse findings of 35 sample studies comprising 148 correlations, we performed a random effect model of meta-analysis to summarize the effect sizes of pairwise relationships. The findings revealed the attitude as a most crucial antecedent of behavioral intention. The second most associated construct with intention was subjective norms followed by perceived behavior control. Subgroup analysis revealed that human development level and cultural factors significantly moderate some TPB linkages. This study provides valuable insights to the literature in two ways; first, it supports the utility of the TPB in the green energy domain. Second, it provides evidence on under what circumstances the consumers' attitude, social norms and control beliefs toward green energy will affect their behavioral intentions. Accordingly, the study offers practical implications and recommendations for future research.